Lead uptake by new silica-carbon nanoparticles - Hammud, Hassan Hasan; Chahine, Mayssam Mostafa; El-Hamaoui, Bassem; Hanifehpour, Younes (European Journal of Chemistry, 2013)
Silica-carbon nanoparticles (SCNP) were prepared from sonication of silica and anthracene. The size of homogenous nanoparticle is around 5-20 nm confirmed by Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). SEM analysis indicated surface porosity. SCNP were used to remove lead ions (Pb(II)) from aqueous solutions. Adsorption isotherm of Pb(II) on SCNP was well fitted in terms of the Freundlich and Langmuir models. The maximum adsorption capacity of SCNP for Pb(II) was found to be 385 mg/g (1.86 mmol/g) in batch experiment. Thermodynamic studies indicated that sorption process of lead onto SCNP was spontaneous and exothermic. A pseudo-second order model has been employed in order to describe the kinetic adsorption processes, and the thermodynamic activation parameters were calculated. In a column studies, qy the Yan adsorption capacity of SCNP for Pb(II) was found to be 130.66 mg/g (0.63 mmol/g).